2014
DOI: 10.1186/1471-2474-15-89
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder diagnoses in secondary care, a one year cohort

Abstract: BackgroundShoulder pain is common in the general population. Reports on specific diagnoses in general populations are scarce and only from primary care. The diagnostic distribution of shoulder disorders in secondary care is not reported. Most of the clinical research in the shoulder field is done in hospital settings. The aim of this study was to identify the diagnoses in a 1-year cohort in a hospital-based outpatient clinic using standardized diagnostic criteria and to compare the results with previous studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
69
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 30 publications
5
69
1
6
Order By: Relevance
“…1,16,17 GH arthritis was seen in 10.0% of cases and rotator cuff injury was 13.1% in our study which is slightly higher than reported by other worker. 18 But this agrees well with the fact that we expect a higher proportion of cases with a definite diagnosis in patients referred to a tertiary care centre as compared to a primary and secondary care centre.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…1,16,17 GH arthritis was seen in 10.0% of cases and rotator cuff injury was 13.1% in our study which is slightly higher than reported by other worker. 18 But this agrees well with the fact that we expect a higher proportion of cases with a definite diagnosis in patients referred to a tertiary care centre as compared to a primary and secondary care centre.…”
Section: Discussionsupporting
confidence: 76%
“…17 Most of the studies have reported subacromial pain syndrome as the most common cause of pain ranging from 30% to 86% of cases but we found subacromial pain in only 13.8% cases. 1,[16][17][18] The three previous studies reporting results of primary care centre population do not mention rotator cuff injury or GH arthritis as cause of shoulder pain. 1,16,17 GH arthritis was seen in 10.0% of cases and rotator cuff injury was 13.1% in our study which is slightly higher than reported by other worker.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Çalış-mamızda hastaların 79'u erkek, 163'ü kadındı. Ağrı hastayı hekime getiren en önemli semptomdur, özellikle de ağrı nedeniyle hekimlere en fazla baş-vuruyu kadınlar yapar.…”
Section: Discussionunclassified
“…SSS'de dominant taraf ile tutulan taraf arasında ilişki saptanmamıştır. 13,14 Çalışmamızda da ilişkili bulgu yoktu. SSS'nin etiyolojisi sadece dış etkenlere bağlı olsaydı SSS'nin dominant tarafta görülmesi gerekirdi.…”
Section: Discussionunclassified
“…У 766 норвежских больных, предъяв-лявших жалобы на боль в плече, наиболее распростра-ненными диагнозами были субакромиальный синдром (36%), миалгия (17%) и адгезивный капсулит (11%). Первичный артроз плечевого сустава в данном исследо-вании встречался всего в 4% случаев и только у лиц стар-ше 60 лет, при этом не имелось гендерных различий [18]. В данной возрастной группе не следует забывать о такой социально значимой проблеме, как остеопороз.…”
unclassified